PENEGAKAN HUKUM TINDAK PIDANA PERDAGANGAN ORANG DALAM (INSIDER TRADING) DI PASAR MODAL - Aji Sena Pamungkas; Indah Kusuma Wardhani (Fakultas Hukum Universitas Borobudur, 2024)
In the midst of the increasingly developing dynamics of the capital market, law enforcement against insider trading in the capital market is a significant challenge. This crime not only harms many parties, but also threatens the credibility of the industry as a whole. This study will discuss the problems regarding the causes of insider trading and law enforcement against insider trading in the capital market. The approach method used in this study is normative juridical. The results of the study show that the occurrence of insider trading is caused by several things, including stock price fluctuations, the role of insiders, and a narrow understanding of the general principles of securities transactions. Law enforcement against insider trading cannot run optimally, including because Law Number 8 of 1995 concerning the Capital Market as amended by Law Number 4 of 2023 concerning the Development and Strengthening of the Financial Sector still adheres to the fiduciary duty theory, thus causing difficulties in proving and enforcing the law on insider trading. The limited authority of OJK investigators, the number of OJK investigators is too small, and inadequate facilities and infrastructure cause the process of examining and investigating insider trading crimes to be ineffective. The lack of public knowledge about insider trading crimes also provides an opportunity for many parties to carry out fraudulent practices in order to seek personal gain.